2010
DOI: 10.6009/jjrt.66.1423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Image Quality Using the Normalized-Rank Approach for Primary Class Liquid-Crystal Display (LCD) Monitors with Different Colors and Resolution

Abstract: The purposes of this study were to evaluate the image quality of five types of liquid-crystal display (LCD) monitors by utilizing the normalized-rank approach and to investigate the effect of LCD monitor specifications, such as display colors, luminance, and resolution, on the evaluators' ranking. The LCD monitors used in this study were 2, 3 and 5 mega-pixel monochrome LCD monitors, and 2 and 3 mega-pixel color LCD monitors (Eizo Nanao Corporation). All LCD monitors were calibrated to the grayscale standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…We established some technical differences, but like Samei et al, we could not find any statistically significant differences in radiological assessments made with different LCDs 5. This was consistent with most reported studies, where no diagnostic differences were found between LCDs with different specifications 5,6,8,912,1416…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We established some technical differences, but like Samei et al, we could not find any statistically significant differences in radiological assessments made with different LCDs 5. This was consistent with most reported studies, where no diagnostic differences were found between LCDs with different specifications 5,6,8,912,1416…”
Section: Discussionsupporting
confidence: 90%
“…Deterioration of the color filters in color LCDs might lead to rapid decreases in luminance 8. Kuroki et al suggested that the luminance of LCDs affected observer evaluations 6. Second, our radiological assessments were based on AAPM TG-18 criteria, but we did not investigate specific diagnostic criteria.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations